FRACTURE TOUGHNESS ASSESSMENT OF DEEP WELL ROCK USING CCNBD AND SCB TEST PROTOCOLS - Ghomesheh, P. K.; Hosseini, A.; Fathi, A. (Journal of Fundamental and Applied Sciences, 2019)
Fracture mechanics is widely deployed in stone fracture modeling, digging with hydraulic, and dynamic fracture techniques for assessing the effects of rock fracture mechanical properties on different hydraulic fracture digging process. To get a better insight about the process, testing the actual rock samples can be extremely imperative. This study, indeed, attempts to evaluate the fracture toughness of actual rock samples using two different test protocols, i.e., Cracked Chevron Notched Brazilian Disc (CCNBD) and Semi-Circular Bend (SCB). The results indicate that similar behavior is observed for the samples under the two tests. However, due to the geometry, created a crack, and the loading conditions of the prepared samples, the fracture occurs for the SCB samples under a less needed force. The results also indicate that the SCB test samples yield more fracture toughness.